2012
DOI: 10.1371/journal.pone.0050235
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Mangafodipir Improves Liver Graft Tolerance to Ischemia/Reperfusion Injury in Rat

Abstract: Ischemia/reperfusion injury occurring during liver transplantation is mainly due to the generation of reactive oxygen species (ROS) upon revascularization. Thus, delivery of antioxidant enzymes might reduce the deleterious effects of ROS and improve liver graft initial function. Mangafodipir trisodium (MnDPDP), a contrast agent currently used in magnetic resonance imaging of the liver, has been shown to be endowed with powerful antioxidant properties. We hypothesized that MnDPDP could have a protective effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…Twenty-six of included 40 articles are observational studies [14,, while the remaining are interventional studies [7,8,[15][16][17][18][43][44][45][46][47][48][49][50][51]. Nine in vitro cell culture studies were reported using various cell lines.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-six of included 40 articles are observational studies [14,, while the remaining are interventional studies [7,8,[15][16][17][18][43][44][45][46][47][48][49][50][51]. Nine in vitro cell culture studies were reported using various cell lines.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In animal hypoxia models, oxygen concentration was varied from 0% to 21% (asphyxia, hypoxia, and normoxia) with time spans from acute hypoxia to tolerant hypoxia. In 21 IR animal models, 11 adopted 70% liver (left and middle lobe) IR (I: 1-6 h, R: 0.5-12 h) [15,16,23,24,36,37,39,43,46,47,51], 4 liver transplantation induced IR (I: 6-24 h, R: 2 h-14 d) [18,19,44,50] …”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Under hypoxia condition, HIF-1α acting as a key transcription factor is highly expressed and oxygen-free radicals accumulate. Evidence has shown that the expression of HO-1 was increased by HIF-1α (12,13). Moreover, oxidation stress exists in tumors (14).…”
Section: Discussionmentioning
confidence: 99%